INTEGRATED STRATEGY OF INNOVATIVE DEVELOPMENT OF AGRICULTURE - NISHCHAKOV, Ihor; KHOLODIUK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Innovations are a key factor in the development of agriculture in Ukraine and in the world in general. Globalization and the dynamics of the world economy require the implementation of effective innovative strategies to ensure the competitiveness of the agricultural sector of Ukraine. The introduction of innovations in agriculture helps to improve production technologies, update the technical base, reduce costs and increase the efficiency of processes at all stages. The review of the literature in the work confirms the relevance of the topic of innovations in agriculture. The research was conducted using qualitative and quantitative methods. The Scopus and Google Scholar databases were used for the systematization and analysis of scientific sources, and the key selection criteria included relevance, relevance, scientific credibility, methodological quality, citation and impact of works. In addition, the study includes a quantitative analysis of R&D expenditures in Ukraine, particularly in the field of agriculture, the results of which are presented in the form of graphs. The research findings emphasize that the financing of innovative activities is the main catalyst for the development of the agricultural sector of Ukraine, stimulating scientific research, the introduction of the latest technologies and the creation of environmentally safe products. The article proposes a comprehensive strategy that includes the development of innovative infrastructure for scientific research and the creation of conditions for attracting investment through grants, special programs and support of private investors. It is also important to introduce modern technologies — artificial intelligence, data analysis, and process automation — to increase production efficiency and reduce the negative impact on the environment. The development of a network of cooperation between scientific, educational and agricultural institutions stimulates the exchange of knowledge and practical experience, while the improvement of the legislative framework contributes to the creation of favorable conditions for innovative development. All these aspects contribute to the creation of a sustainable, competitive agricultural sector that meets the requirements of the modern consumer and global environmental standards.
Keywords: innovation; technology; agriculture; research and development; strategy